Association between Thyroid Pro?le and Serum Bilirubin Levels in Term Neonates on Day 3 of Life - Prahlad Kadambi; MA Ramprakash; Gandi Soujanya; L Sushanth Prabhath Reddy (Asian Journal of Clinical Pediatrics and Neonatology, 2020)
Background: Neonatal indirect hyperbilirubinemia is a common clinical scenario that manifests as jaundice in the first week of life. Studies have shown that the physiological peak of serum bilirubin (SBR) levels is highest at 72 hours of life as a result of which SBR is measured at  72 hours of life routinely. The American Academy of Pediatricians (AAP) recommends routine screening for congenital hypothyroidism within the first week of life for all neonates. In common practice, both parameters are assessed simultaneously at 72 hours of life. This study aims     to correlate thyroid Profile and serum bilirubin levels assessed in term neonates at 72 hours of life. Subjects and Methods: Our retrospective study included 105 term neonates born through cesarean-section at MMCHRI, Kanchipuram; between August 2018 and August 2019. Pre-term, neonates born to eclamptic, pre-eclamptic, diabetic, hypothyroid, Rh-incompatible mothers were excluded from the study. The data collected included Birth Weight, Gestational Age, Thyroid Profile (T3, T4, TSH), SBR (Total and Direct). Data were analyzed using SPSS v16. Results: The mean gestational age of the study population was 268.05  6.25 days, and mean birth weight was 2.997  0.36 kgs. The mean serum levels  of total bilirubin were 11.36 3.52 mg/dl. The mean serum fT3, fT4, TSH levels were 8.17 23.2 pg/ml, 2.16 1.68 ng/dl and 4.07 3.4 mIU/ml respectively. A positive association was noted between serum TSH and total serum bilirubin (r= 0.176, p = 0.067) but not statistically significant. Conclusion: Our study has not shown a significant association between serum TSH and SBRT in term neonates. However, the simultaneous assessment remains practical in practice.